Stress in parents of children diagnosed with autism spectrum disorder in a private institution, Lima, Peru, 2022 - Periche A, Kenny W. (2024)
Objective: To determine the level of stress in parents of children diagnosed with autism spectrum disorder (ASD) atInstituto para el Desarrollo Infantil (Institute for Child Development) - ARIE, San Juan de Lurigancho (SJL) branch, 2022. Materials and methods: A descriptive and cross-sectional study at Instituto para el Desarrollo Infantil - ARIE, SJL branch. Lima Peru. All parents (n = 79) with children aged ≤ 8 years with ASD who were undergoing therapy in 2022 were included; therefore, sampling was not required. The PSI/SF (Parenting Stress Index, Short Form) was used to measure stress in parents. This instrument has been used in other research studies, validating it with a Cronbach's alpha coefficient of 0.93 to determine parental stress.The variables sex of the parent, sex of the child, age, level of education and type of family were analyzed with SPSS V.27 using descriptive statistics and chi-square test. Results: A total of 79 parents were surveyed: average age 35.20, SD 5.217, predominantly females (68.35 %). Of the parents,73.41 % had higher education. Parental stress perceived by mothers (83.33 %) was slightly higher than that of fathers (60 %) (p < 0.05). There is an association between the level of parental stress and the sex of the child, with males (82.1 %) causing more stress compared to females (60.9 %). Single-parent families have shown a higher level of stress, with 95.46 %, asopposed to two-parent families, with 64.42 %) (p < 0.05). Conclusions: Most parents with children with ASD experience clinically significant stress, with scores greater than 90,with mothers having a higher degree of stress. There is a significant association between parental stress and the sex of the child and the type of family (p < 0.05).